1939
DOI: 10.1021/ja01267a002
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Vinyl Polymers. VII. Polyacrylyl Chloride

Abstract: polymer which does not decolorize aqueous potassium permanganate solution. Polyvinyl halides do not liberate iodine from potassium iodide. The ultraviolet absorption spectrum of polyvinyl chloride is very similar to that of 2,4-dichloro-pentane and somewhat different from that of 2,3dichloropentane. All of these facts support the view that polyvinyl chloride has the 1,3-dihalide structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1940
1940
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Polyvinyl methyl ketoxime (15) was prepared from the incompletely polymerized mixture with excess hydroxylamine the reaction product of the monomer remaining soluble. The polyoxime was soluble in dilute strong alkali or acid; no other solvents were found.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyvinyl methyl ketoxime (15) was prepared from the incompletely polymerized mixture with excess hydroxylamine the reaction product of the monomer remaining soluble. The polyoxime was soluble in dilute strong alkali or acid; no other solvents were found.…”
Section: Experimental Partmentioning
confidence: 99%
“…The fifth source of polyvinylamine which was investigated was the Beckmann rearrangement of polyvinyl methyl ketoxime XIII, previously prepared by Marvel and Levesque (15). The present authors found it desirable to carry out the polymerization of the vinyl methyl ketone in concentrated dioxane solution in order to ensure obtaining a soluble polymer.…”
mentioning
confidence: 93%
“…The production of acid amides by the action of liquid ammonia on lactones has been reported for the following cases: d-ct.a-mannooctoniclactone (47), 2,3,4-trimethyl d-mannonolactone (47a), 4,6-dimethyl-d-galactonolactone (48), 2,4,6-trimethyl-d-iodono-S-lactone (49). The polymer prepared by the action of a boron fluorideether complex on a-angelica lactone has been found to react with a mixture of dioxane and liquid ammonia at 150-160°to form a polylactam (50).…”
Section: Ammonolysismentioning
confidence: 99%
“…Free radical polymerizations of acryloyl chloride (AC) [12][13][14][15][16][17][18] and methacryloyl chloride (MAC) [19][20][21] have been known as a means to produce poly(acryloyl chloride) (PAC) and poly(methacryloyl chloride) (PMAC), respectively. 22 Since polymers with a smaller but controlled number of reactive groups are oen more attractive for synthetic purposes, 22 copolymerization of AC [15][16][17][23][24][25][26] and MAC 22,27,28 with non-reactive monomers such as methyl methacrylate has been also studied.…”
Section: Introductionmentioning
confidence: 99%